Quercetin Supplementation Reduces Oxidative Stress in the Testes of Wistar Rats Fed a High-Fat Diet - de Oliveira Santos, Aline; Quadreli, Debora Hipolito; Fernandes, Glaura Scantamburlo Alves; de Souza Reis, Luis Souza Lima; de Andrade Bernal Fagiani, Marcela; Marin, Lauren Chrys Soato; Batista, Victor Rogério Garcia [UNESP]; Teixeira, Giovana Rampazzo [UNESP]; de Lima Paz, Patrik Junior [UNESP]; Castilho, Caliê; de Oliveira Vidotto Figueiredo, Mayara; Giometti, Ines Cristina (Wiley, 2025)
Problem: A high-fat diet (HFD) predisposes animals to glucose intolerance, dyslipidemia and testicular oxidative stress, and impairs sperm production in rats. Quercetin is a flavonoid with antioxidant, anti-inflammatory, and lipolytic actions and is a potential supplement to combat the oxidative stress caused by HFD and its harmful effects on reproduction. This study evaluated the effects of quercetin supplementation at doses of 10 and 20 mg/day on reproductive parameters and testicular oxidative stress in Wistar rats fed a diet rich in pork fat and fructose. Method of study: The rats received a basal diet or HFD for 2 months, after which the animals fed the HFD received daily supplementation of 0, 10, or 20 mg of quercetin for another 2 months. Oxidative stress, histological alterations, and the expression of oxidative, inflammatory, and apoptotic mediators in the testes were evaluated. Results: Animals fed the HFD had a lower dietary intake and body, epididymis, and duct weights, regardless of the presence of quercetin. There were no changes in testicular weight, germinal epithelium diameter, sperm motility and morphology, or expression of testicular inflammatory genes (p > 0.05). There was a reduction in the oxidative stress index and oxidized glutathione in rats that received the HFD and 20 mg of quercetin compared with the HF group without quercetin. No difference was observed in the expression of BAX, BCL2, TNFα, caspase 3, or AR between the groups. Conclusion: Daily quercetin supplementation dose-dependently reduces testicular oxidative stress in Wistar rats fed a diet rich in pork fat and fructose.
Keywords: antioxidants; catalase; glutathione; MDA; sperm; TBARs